Formulation and Anti-Hypertensive Activity of Ambon Banana Peel Foam Mat Drying Granules as a Nutraceutical - Arifin, Ibrahim; Anwar, Khoirul; Shabrina, Ayu; Wibowo, Danang Novianto; Amirudin, Muhammad Subhan; Kumalasari, Wahyu; Angelita, Anastasya; Mastuti, Sri; Inayati, Dian (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Ambon banana peel (ABP) is rich in phenolic compounds yet unstable to light and heat. Foam-mat drying (FMD) protects bioactive components and facilitates the development of nutraceutical products. This study aimed to formulate and evaluate FMD granules containing ABP for their antioxidant and antihypertensive activities. Granules were prepared with ABP at 1% (F1), 2.5% (F2), and 5% (F3) w/w, combined with 6% Tween-80 and 15% maltodextrin, dried at 40 °C for 60 min, and blended with excipients. Physical characteristics, pH, flowability, and antioxidant activity (ABTS assay) were assessed. Antihypertensive effects were tested in Wistar rats induced with 2% NaCl and treated orally for 14 days; captopril (5 mg/kg BW) served as a positive control. Data were analyzed by one-way ANOVA. All formulations produced free-flowing granules with a moisture content <2% and a dissolution time <5 min. Antioxidant inhibition increased with ABP content, with F3 showing the highest activity (71.3 ± 1.4%). F3 also achieved the greatest reductions in systolic (≈31%) and diastolic (≈39%) blood pressure, approaching the effect of captopril. Moreover, F3 exhibits strong antioxidant activity and significant antihypertensive effects, indicating potential as a sustainable nutraceutical for the management of hypertension. Further studies on product stability and clinical efficacy are warranted.